The Alternative Model Policies to Reduce the Impact of Climate Change - Warlina, Lina; Listyarini, Sri (International Journal of Engineering and Technology, 2018)
Currently, climate change is one of the highlights from the world's attention because of the impact of climate change in life. Research related policies to reduce these impacts are still not widely practiced, especially in Indonesia. The purpose of this study was to develop a model of policy alternatives that can be used as a reference in the response to climate change impacts on environmental and economic aspects. There are 2 methods used in this research, first is a dynamic simulation model using VENSIM software and the second is model of policy analysis using Multi Criteria Decision Analysis (MCDA) method with software PRIME for developing policy alternatives. The results showed that policy that based on economy, namely the reduction of the amount of fuel, is a policy that can reduce CO2 emissions significantly compared with the policy that based on environment is the addition of green open space.Â Â